Exceptional bodies in early modern culture : concepts of monstrosity before the advent of the normal - Bondestam, Maja (Amsterdam : Amsterdam University Press, 2020)
Drawing on a rich array of textual and visual primary sources-including medicine, satire, play script, dictionaries, natural philosophy, and texts on collecting wonders-this book provides a fresh perspective on monstrosity in early modern European culture. The essays explore how exceptional bodies challenged social, religious, sexual and natural structures and hierarchies in the sixteenth-, seventeenth- and early eighteenth centuries and contributed to its knowledge, virtue and emotional repertoire. Prodigious births, maternal imagination, hermaphrodites, collections of extraordinary things, powerful women, disabilities, controversial exercise, shapeshifting phenomena, and hybrids of different kinds are examined in a period before all deviances became normalized, in the sense, close and relative to a homogenous standard. The historicizing of exceptional bodies is central in the volume since it brings out the early modern culture and deepen our knowledge of its specific ways of conceptualizing singularities, rare examples, paradoxes, rules and conventions in nature and society.
Frontmatter -- Table of Contents -- List of Illustrations -- Introduction -- 1. The Moresca Dance in Counter- Reformation Rome: Court Medicine and the Moderation of Exceptional Bodies -- 2. Monsters and the Maternal Imagination : The 'First Vision' from Johann Remmelin's 1619 Catoptrum microcosmicum Triptych -- 3. The Optics of Bodily Deviance : Juan Ruiz de Alarcón's Path to Public Office -- 4. 'The Most Deformed Woman in France' : Marguerite de Valois's Monstrous Sexuality in the Divorce satyrique -- 5. Curious, Useful and Important: Bayle's 'Hermaphrodites' as Figures of Theological Inquiry -- 6. An Education: Johannes Schefferus and the Prodigious Son of a Fisherman -- 7. Ambiguous and Transitional Bodies: Stillbirth in Stockholm, 1691-1724 -- Afterword -- Index
Online resource; title from digital title page (viewed on December 08, 2020).
JSTOR
Keywords: Abnormalities, Human -- Social aspects; Monsters -- Social aspects; Abnormalities, Human, in literature; Monsters in literature; Abnormalities, Human; Monsters; Monstres -- Aspect social; Monstres dans la littérature.; Monstres; HISTORY -- Renaissance; Abnormalities, Human; Abnormalities, Human, in literature; Abnormalities, Human -- Social aspects; Monsters; Monsters in literature; early modern, culture, monstrosity, bodies, normalization; Electronic book